ANALISIS RISIKO NILAI TUKAR MATA UANG ASING TERHADAP PROFITABILITAS BANK UMUM NASIONAL DI INDONESIA - Panggabean, Priska Basariana (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
Bank’s exposure to market risks significantly affects bank's income, profit and return even though it is not its primary source of income. This study will analyze the relationship between foreign exchange rate risk using the Value at Risk method against the rate of return on assets invested by banks. The data used is sourced from data on the Net Open Position of 5 Banks in Indonesia in 2021, 2022, 2023 in 5 foreign currencies, calculated with Value at Risk approach in portfolio currencies, as the independent variables. Regression analysis was carried out simultaneously with the financial ratios of CAR, NPL, and NIM as control variables. The results obtained showed that the increase in foreign exchange rate risk with the Value at Risk method along with CAR and NIM have a positive correlation with the increase in RoA and the NPL ratio had a negative correlation with the increase in RoA.